SISTEM INFORMASI AKUNTANSI PADA KUALITAS LAPORAN KEUANGAN UMKM (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2023)
The purpose of this study is to determine how much influence the Accounting Information System has on the Quality of MSME Financial Reports in Coblong District, Bandung City. The research method used in this study is a descriptive and verification method with a quantitative approach. The sample in this study were 39 SMEs in Coblong District, Bandung City. The data source in this study is primary data obtained from the answers to the respondent's questionnaire. The results in this study are that the Accounting Information System has a positive influence on the quality of MSME financial reports, which means that if the Accounting Information System increases, it will improve the Quality of MSME Financial Reports. Keywords: Accounting Information Systems, Quality of Financial Reports, MSMEs